El trabajo pliométrico y sus efectos en las deportistas de la selección de baloncesto de tercera categoría del colegio Instituto Tegnológico Superior Iabel de Godín periodo 2011- 2012 - Parrales Moreira, Holger Omar (2013)
Plyometrics is a type of training designed to produce fast, powerful movements. They are usually used to improve speed, quickness and strength in athletes. The use of explosive and quick movements to develop muscular strength and improve overall speed is the main goal of plyometric work, because it involves exercises that allow muscles run the maximum force in the least amount of time. The development of strength in the legs can increase the performance of the player and, likewise, improve performance in competition. Plyometrics is considered a factor that can be applied correctly in the young players in pursuit of better performance in sports. The research paper entitled "The plyometric work and its effects on the performance of athletes Basketball Selection third category of Higher Technological Institute Isabel Godin, 2011-2012 period", had as main objective to determine the relationship between the application of a training program based on plyometrics and sports performance.